Clustering of smoking, alcohol drinking and cannabis use in adolescents in a rapidly developing country - Chiolero Arnaud; Warren Wick; Viswanathan Bharathi; Faeh David; Bovet Pascal (BMC, 2006)
Abstract Background Smoking, alcohol drinking and cannabis use ("risk behaviors") are often initiated at a young age but few epidemiological studies have assessed their joined prevalence in children in developing countries. This study aims at examining the joint prevalence of these behaviors in adolescents in the Seychelles, a rapidly developing country in the Indian Ocean. Methods Cross-sectional survey in a representative sample of secondary school students using an anonymous self-administered questionnaire (Global Youth Tobacco Survey). The questionnaire was completed by 1,321 (92%) of 1,442 eligible students aged 11 to 17 years. Main variables of interest included smoking cigarettes on ≥1 day in the past 30 days; drinking any alcohol beverage on ≥1 day in the past 30 days and using cannabis at least once in the past 12 months. Results In boys and girls, respectively, prevalence (95% CI) was 30% (26-34)/21% (18-25) for smoking, 49% (45-54)/48% (43-52) for drinking, and 17% (15-20)/8% (6-10) for cannabis use. The prevalence of all these behaviors increased with age. Smokers were two times more likely than non-smokers to drink and nine times more likely to use cannabis. Drinkers were three times more likely than non-drinkers to smoke or to use cannabis. Comparison of observed versus expected frequencies of combination categories demonstrated clustering of these risk behaviors in students (P < 0.001). Conclusion Smoking, drinking and cannabis use were common and clustered among adolescents of a rapidly developing country. These findings stress the need for early and integrated prevention programs.